2021
DOI: 10.1007/s12298-021-00984-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glutamic acid foliar applications on lettuce under water stress

Abstract: The yield and quality of leafy vegetables can be compromised by reduced water availability. Glutamic acid is involved in different biological processes and among them it plays an important role in chlorophyll and proline biosynthesis. The aim of this work was to evaluate the possible efficacy of glutamic acid in counteracting water stress in romaine lettuce. Lettuce plants were grown in pots filled with substrate and subjected to water deprivation. A glutamic acid solution (1.9 mM) was applied as foliar treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 72 publications
2
9
0
1
Order By: Relevance
“…A similar result, suggesting a connection between the glutamic acid and LsSOD was also observed in a previous work where glutamic acid was applied on lettuce plants subjected to a period of water deprivation (Franzoni et al, 2021). Moreover, further experiments aimed to clarify this aspect are necessary.…”
Section: Declaration Of Competing Interestsupporting
confidence: 84%
“…A similar result, suggesting a connection between the glutamic acid and LsSOD was also observed in a previous work where glutamic acid was applied on lettuce plants subjected to a period of water deprivation (Franzoni et al, 2021). Moreover, further experiments aimed to clarify this aspect are necessary.…”
Section: Declaration Of Competing Interestsupporting
confidence: 84%
“…Changes in photosynthetic pigments and subsequently in chlorophyll fluorescence attributes may lead to an alteration in photosynthetic efficiency, including the capability to harvest light; hence, observing these traits is essential to determine the plant photosynthetic effectiveness. In the current research, a differential trend was observed in the chlorophyll content, which was positive in the case of plants primed with tap water and Fe-10 mM, which may be attributed to simultaneous changes in osmoprotectant and different response levels of the studied wheats. …”
Section: Discussionmentioning
confidence: 46%
“…In this respect, Khan et al (2019) revealed that treated lettuce plants with amino acid significantly increased the chemical constituents (N,P and K as well as dry matter contents) in lettuce plants. In this regard, Franzoni et al (2020) found that spraying lettuce plants with amino acid reduced nitrate accumulation in leaves than unsprayed plants.…”
Section: Effect Of Tryptophanmentioning
confidence: 96%